2020
DOI: 10.2147/nss.s275051
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Associations of Gender, Menopause, Age, and Asthma with REM-Predominant Obstructive Sleep Apnea: A Prospective Observational Study</p>

Abstract: The study sought to assess demographics, clinical features, comorbidities, and polysomnographic features of a large cohort of clinic-based patients with rapid eye movementpredominant obstructive sleep apnea (REM-predominant-OSA) in both genders, while assessing the relationship between REM-predominant OSA in one hand and menopausal status and age on the other. Methods: This prospective observational study was conducted between January 2003 and December 2017. REM-predominant OSA diagnostic criteria included an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 41 publications
8
22
3
Order By: Relevance
“…Likewise, the logistic regression confirmed that age < 60 years and female gender were independent correlates of REM-related OSA. These results are consistent with other studies 5 , 7 , 19 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Likewise, the logistic regression confirmed that age < 60 years and female gender were independent correlates of REM-related OSA. These results are consistent with other studies 5 , 7 , 19 .…”
Section: Discussionsupporting
confidence: 94%
“…The association between REM-related OSA and asthma was interesting because a prospective observational study showed that asthma was independently associated with REM-related OSA 19 , which was consistent with a previous study in children with OSA 31 , while our results showed a negative relationship. However, the published pathophysiologic mechanisms that explain the association between asthma and OSA, especially REM-related OSA, are not well understood and are limited.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A study attempted to determine whether REM-OSA is related to age or menopausal status in women. Premenopausal status and age were associated with REM-OSA among women in the univariate analysis model; however, only age remained an independent correlate of REM-OSA in the multivariable model [12 ▪▪ ].…”
Section: Definition and Epidemiology Of Rapid Eye Movement-predominan...mentioning
confidence: 79%
“…In addition, it is important to note that dopaminergic treatment in PD may lead to an underestimation of RLS (dopamine agonists reduce RLS) or an overestimation of RLS (longterm treatment may cause augmentation and unmask subclinical RLS). In a study of 80 PD patients, 30 PD patients with RLS were older and had a longer duration of PD, higher nonmotor symptom scores (NMSQ), and a higher rate of impulse control disorders (50% vs. 26%), and RLS was an independent risk factor for impulse control disorders (odds ratio 5.9) after adjusting for confounding factors to younger age, female sex, asthma [160] and lateral positioning during sleep [161].…”
Section: Rls With Pdmentioning
confidence: 99%